Financial crises in comparative perspective: Crisis management and its phenomenon of repetition/return - Sebastian Zemla (Naše gospodarstvo / Our Economy, 2020)
Crises cause attentiveness in our society and awaken, depending on the degree of consternation, our ongoing interest. These events include financial crises, phenomenal incidents that shock the economic world and pose significant challenges for the governments. Two crises which stand out in this context are the Great Depression in 1929 and the financial crisis in 2007/2008. In addition to the comparative approach, the paper focuses directly on the typical repetitive mechanism ("recurrent pattern of banking and sovereign debt crises" (Reinhart & Rogoff, 2011): overheating, the forming of a bubble and the bursting of the bubble, largely started in the USA. Specific aspects included in this research area are crisis management in the decades mentioned above, the role of governments and banks, as well as the observation as to which crisis can be expected next. We can conclude that the current monetary systems led by complex financial instruments and addicted to low interest rates are prone to deliver another serious financial crisis.
Keywords: G15; G18; G21; O16; N2; 330; financial crises; comparison of crises; crisis management; government measures; future inevitability